Cost–Utility Analysis of rhBMP-2 Use in Adult Spinal Deformity Surgery. Issue 14 (15th July 2020) - Jain, Amit; Yeramaneni, Samrat; Kebaish, Khaled M.; Raad, Micheal; Gum, Jeffrey L.; Klineberg, Eric O.; Hassanzadeh, Hamid; Kelly, Michael P.; Passias, Peter G.; Ames, Christopher P.; Smith, Justin S.; Shaffrey, Christopher I.; et al.
Abstract : Study Design: Economic modeling of data from a multicenter, prospective registry. Objective: The aim of this study was to analyze the cost utility of recombinant human bone morphogenetic protein-2 (BMP) in adult spinal deformity (ASD) surgery. Summary of Background Data: ASD surgery is expensive and presents risk of major complications. BMP is frequently used off-label to reduce the risk of pseudarthrosis. Methods: Of 522 ASD patients with fusion of five or more spinal levels, 367 (70%) had at least 2-year follow-up. Total direct cost was calculated by adding direct costs of the index surgery and any subsequent reoperations or readmissions. Cumulative quality-adjusted life years (QALYs) gained were calculated from the change in preoperative to final follow-up SF-6D health utility score. A decision-analysis model comparing BMP versus no-BMP was developed with pseudarthrosis as the primary outcome. Costs and benefits were discounted at 3%. Probabilistic sensitivity analysis was performed using mixed first-order and second-order Monte Carlo simulations. One-way sensitivity analyses were performed by varying cost, probability, and QALY estimates (Alpha = 0.05). Results: BMP was used in the index surgery for 267 patients (73%). The mean (±standard deviation) direct cost of BMP for the index surgery was 14, 000 ± 6400. Forty patients (11%) underwent revision surgery for symptomatic pseudarthrosis (BMP group, 8.6%; no-BMP group, 17%; P = 0.022). The mean 2-year direct cost was significantly higher for patients with pseudarthrosis (138, 000 ± 17, 000) than for patients without pseudarthrosis (61, 000 ± 25, 000) ( P < 0.001). Simulation analysis revealed that BMP was associated with positive incremental utility in 67% of patients and considered favorable at a willingness-to-pay threshold of 150, 000/QALY in >52% of patients. Conclusion: BMP use was associated with reduction in revisions for symptomatic pseudarthrosis in ASD surgery. Cost–utility analysis suggests that BMP use may be favored in ASD surgery; however, this determination requires further research. Level of Evidence: 2 Abstract : Among patients who underwent adult spinal deformity (ASD) surgery, the rate of symptomatic pseudarthrosis was significantly higher in the no-bone morphogenetic protein-2 (BMP) group (17%) compared with the BMP group (9%). Cost–utility analysis suggests that BMP use may be favored in ASD surgery; however, this determination requires further research.